Kelayakan Laboratorium Biologi Sebagai Penunjang Kegiatan Praktikum Di SMA Muhammadiyah 1 Dan 2 Surakarta Tahun 2015 - Nur Fauzi, Riris; , Dr. Sofyan Anif, M.Si (2015)
Many school there are not fully realized importace of Biologi lab in accordance with standards government has set. This research have to knowexpediency biology laboratories as supporting practical work activity at SMA Muhammadiyah 1 and 2 Surakarta and compare expediency biology laboratories as supporting practical work activity at SMA Muhammadiyah 1 and 2 Surakarta. This research constitute qualitative descriptive research. Subjects in this research were laboratory personnel biology teachers, while the objects of research is biology laboratories. Data was collected through observation, structured interview, and documentation. The test result of the research descriptive qualitative expediency laboratories at SMA mentioned show (1) design space biology laboratories at SMA Muhammadiyah 1 and 2 Surakarta average already good enough, percentage yield observation sheet and 50% and yield on the structured interview 60%, (2) facility biology laboratories percentage 95%(very good) and 99% (very good), (3) completeness of material biology laboratory based on the observation sheet, already meet minimal standards as big as 100% categorized as very good, 4) administration of an average of biology lab at SMA Muhammadiyah 1 and 2 Surakarta each 86,35% (good)and 72,7% (good), 5) the management organization of the practical at SMA Muhammadiyah 1 and 2 Surakarta each72,25% (good) dan 89% (very good), 6) biology teaching activities at SMA Muhammadiyah 1 and 2 Surakarta same 84,2% (very good). Biology laboratories at SMA Muhammadiyah 1 and 2 Surakarta categorized in both practical support.